(untitled) (Research, Society and Development, 2023)
Dental darkening occurs due to chromophores impregnated in the tooth structure for several reasons, such as trauma, endodontic treatment, hemorrhages in the internal structure of the teeth. When these pigments form a molecule capable of reflecting light at a wavelength visible to the human eye and whose intensity is greater than the light reflected by the tooth structure, a darkened tooth is observed. Therefore, the demand for tooth whitening increases, becoming a possibility for aesthetic treatment that offers greater preservation of the tooth structure. The objective of the work is a literature review, with the purpose of understanding aesthetic treatment techniques, The present study corresponds through a survey of bibliographic sources. However, the desire to have a harmonious and especially brighter smile ended up making one of the whitening procedures the first treatment option. After using tooth whitening and not achieving the desired aesthetics, composite resin veneers are chosen, which are considered one of the fastest, safest and most effective techniques.